A compact slot antenna configuration for ultrawideband (UWB) terminals and mobile phones. Issue 8 (25th April 2018) - Zong, Wei‐Hua; Yang, Xiao‐Mei; Li, Shandong; Qu, Xiao‐Yun; Wei, Xiang‐Yang
Abstract: A novel technique to design a mobile phone antenna by using an ultrawideband (UWB) antenna configuration is proposed. The technique is validated with a novel printed slot antenna configuration. The slot is composed of a circle connected to a trapezoid and fed by means of a 50 Ω microstrip line connected to a patch with similar shape to the slot. An UWB antenna with size of 19 mm × 24 mm and measured −10 dB bandwidth of 2.97‐11.32 GHz is developed based on the configuration. When the configuration is applied in a system circuit board of 60 mm × 115 mm to design a mobile phone antenna, the simulated −6 dB bandwidths are 1.0‐1.2 GHz and 2.25‐15 GHz. To enhance antenna bandwidth, another slot with rectangular shape is etched in the ground plane, and the microstrip line is moved to the center of the circuit board and folded to distribute along the rectangular slot. The measured −6 dB bandwidths of the mobile phone antenna are 0.69‐1.09, 1.68‐2.75, 3.45‐3.52, and 3.62‐15 GHz.